Meta‐analysis: Enhanced liver fibrosis test to identify hepatic fibrosis in chronic liver diseases. Issue 7 (17th January 2023) - Hinkson, Alexander; Lally, Hannah; Gibson, Hannah; Jones, Rebecca; Rowe, Ian A.; Shinkins, Bethany; Parker, Richard
Summary: Background & Aims: Patients with liver disease can be stratified for risk of liver‐related ill health by degree of hepatic fibrosis. The Enhanced liver fibrosis (ELF) test was developed to quantify hepatic fibrosis non‐invasively and is widely used. The objective of this review was to identify and synthesise the evidence on the diagnostic accuracy of the ELF test for staging of hepatic fibrosis. Approach & Results: Searches of PubMed and EMBASE were conducted between October 2020 and November 2021 to identify studies reporting the diagnostic accuracy of the ELF test compared to histology in liver disease patients. QUADAS‐2 was used to assess risk of bias in each study. Meta‐analysis using the multiple thresholds model described by Steinhauser S, Schumacher M, Rücker G. Modelling multiple thresholds in meta‐analysis of diagnostic test accuracy studies. BMC Med. Res. Methodol. 2016;16 . 10.1186/s12874‐016‐0196‐1 allowed synthesis of 2 × 2 data at different cut‐offs. Sixty‐three studies were included in this review. These studies included 19, 285 patients with or at risk of liver disease from viral hepatitis, Non‐Alcoholic Fatty Liver Disease, Alcohol‐related Liver Disease and other mixed chronic liver diseases. The prevalence of significant fibrosis, advanced fibrosis and cirrhosis was 47.5%, 39.2% and 4.4%, respectively. Cut‐offs with maximal Youden index were generated with AUROC = 0.811 (95% CI: 0.736–0.870), 0.812 (95% CI: 0.758–0.856) and 0.810 (95% CI: 0.694–0.888) to detect significant fibrosis, advanced fibrosis or cirrhosis, respectively. Diagnostic accuracy of the ELF test varied between different liver diseases and cut‐offs to detect each stage with 95% sensitivity or specificity were also generated. Conclusions: Meta‐analysis revealed considerable variability in the ability of ELF to stage fibrosis across disease aetiologies. Research has mostly focused on viral hepatitis and NAFLD. There is currently a lack of data on the value of the ELF test in Alcohol‐related liver disease and patients in primary care settings. Abstract : Meta‐analysis of data regarding the enhanced liver fibrosis test to yields novel cut‐offs. These include disease‐specific cut‐offs and cut‐offs to detect each disease stage with 95% sensitivity or 95% specificity.